Aharonov-Bohm effect for excitons in a semiconductor quantum ring dressed by circularly polarized light - Kibis, Oleg Vasilyevich (2015)
We show theoretically that the strong coupling of circularly polarized photons to an exciton in ringlike semiconductor nanostructures results in physical nonequivalence of clockwise and counterclockwise exciton rotations in the ring. As a consequence, the stationary energy splitting of exciton states corresponding to these mutually opposite rotations appears. This excitonic Aharonov-Bohm effect depends on the intensity and frequency of the circularly polarized field and can be detected in state-of-the-art optical experiments.